THE INFLUENCE OF PRINCIPAL LEADERSHIP, SCHOOL POLICIES, AND TEACHER PERFORMANCE ON THE QUALITY OF ELEMENTARY SCHOOLS IN ACEH UTARA DISTRICT (SURVEY OF ELEMENTARY SCHOOL SUPERVISORS IN NORTH ACEH REGENCY) - Abdul Hadi; Zainuddin Iba (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This study aims to determine the influence of principal leadership, school policies and teacher performance on the quality of elementary schools in North Aceh District. This type of research is quantitative and uses descriptive analysis methods and causality analysis. The population and sample in this study were 30 elementary school supervisors in North Aceh District. The data analysis technique used is path analysis with SPSS. Based on the results of the descriptive research, it can be concluded that the principal's leadership, school policies, teacher performance and the quality of elementary schools in North aceh district are good. Based on the results of causality research, it can be concluded that the principal's leadership influences school quality, school policy influences school quality, teacher performance influences school quality, school principal's leadership influences school policy, school principal's leadership influences teacher performance, school policy influences performance teacher, the principal's leadership influences school quality through school policy, the principal's leadership influences school quality through teacher performance, school policy influences school quality through teacher performance. Principal leadership, school policies, and teacher performance simultaneously influence the quality of elementary schools in North Aceh District.